Factores de riesgo y su influencia en el asma bronquial en niños que acuden al Centro de Salud “Enrique Ponce Luque” cantón Babahoyo periodo junio - septiembre 2024. - Brunes Sánchez, Susana Stefania (2024)
Bronchial asthma is a chronic disease that affects the bronchi and can occur in people of any age and gender, although it is more common in children, affecting between 5% and 10% of the pediatric population. In some cases, it can be severe and even fatal. It is considered a global health issue, highlighting the importance of identifying and managing associated risk factors. This study aimed to identify risk factors in children aged 2 to 12 years at the Enrique Ponce Luque Health Center. The research employed a quantitative approach, with a descriptive cross-sectional design. A sample of 45 children aged 2 to 12 years diagnosed with asthma was selected, with their parents representing them during the survey process, which was designed to gather the necessary information. The results indicated that environmental risk factors are the main contributors to the development of bronchial asthma. It was concluded that at the Enrique Ponce Luque Health Center, knowledge about bronchial asthma is limited, and the condition was found to be most common in girls aged 7 to 9 years, who received respiratory therapy at home to manage the disease.